Female directors and earnings management: a study from Ireland - Liu, Naijia (2020)
In recent years, the outbreak of a series of financial scandals that shocked the world has triggered the research and thinking of scholars at home and abroad on earnings management which leads to the serious distortion of accounting information. In more than 20 years of research on earnings management behaviour, many scholars have conducted researches on the motivation, means and existence of earnings management from both normative and empirical aspects, and obtained a large number of research results. At present, earnings management is still a hot topic in corporate governance. In recent years, with the wide application of the practical field, scholars have strengthened the research on the influencing factors of earnings management. As the executive of the company is the main manipulator of earnings management, gender diversity has also become an important aspect of earnings management influencing factors.